ANALISIS KONSENTRASI GAS SESAAT DALAM KEMASAN MELALUI LUBANG BERUKURAN MICRO UNTUK MENGEMAS BUAH SEGAR DENGAN SISTIM KEMASAN ATMOSFIR TERMODIFIKASI - Yessy Rosalina (AGROINTEK, 2011)
Fruits can suddenly loose its quality, thus it needs a good packaging material with a suitable permebiality, so that gas exchange inside the packaging normally take place through film packaging. The increasing of permeability on plastic film can be done by giving perforation or a whole on its surface. This research is intended to find out the rate gas exchange through film packaging. In packaging system with modified atmosphire. The result of this research shows that the use of perforation with micro size (50-200 µm) can increase the rate of gas transmission of plastic film toward O. Identification on packaging material which is used reveal that plastic permeability without perforation toward O2 is less than plastic permeability with 10 perforation. Gas equilibrium for 10 perforation packaging resulted on day 21 with gas concentration 0,001% (O2) and 0,000798 % (CO2). The approach by using mathemathic model is done to find out gas concentration inside the packaging during the storage. The model which is developed by Gonzales et al. (2008) nearly close to the result as the observation conducted.